An Antimicrobial Stewardship Initiative to Evaluate Penicillin Allergy Labels in Spinal Cord Injury and Long-Term Care Patients. (4th October 2017) - Hall, Toni; Gauthier, Timothy; Temino, Viviana; Lichtenberger, Paola
Abstract: Background: Inaccurate penicillin (PCN) allergy labels force clinicians to choose less-preferred therapies. Implementation of an inpatient penicillin skin testing (PST) program is one way to assess allergy label validity, but outpatient PST may also play an important role. Within the Miami Veteran Affairs Healthcare System, the Allergy Service and Antimicrobial Stewardship Program (ASP) collaborated to identify and assess PCN allergic patients considered likely to need antibiotics in the future. The purpose of this project is to describe the process and outcomes of this collaboration, targeting Spinal Cord Injury (SCI) and another long-term care patient population. Methods: From April 2016 to February 2017, the ASP pharmacist periodically generated a list of patients admitted to the SCI unit or nursing home with an active PCN allergy label. Patients were screened and an electronic consult was sent to an allergist for evaluation. Data for assessment of the intervention were obtained via a continuous quality improvement project overseen by the ASP and Allergy service. Results: There were 53 patients identified for ASP pharmacist review. Of these, 24 (45%) were referred to the allergist. To date, 13 patients have been evaluated in the outpatient allergy clinic, 6 referrals cancelled and 5 are pending evaluation. Of the 13 patients evaluated, 11 had their allergy label removed and 2 did not. (One patient declined testing and the other was found to have skin anergy.) Eight of 11 negative patients (73%) received antibiotics after label removal and 5 of these patients (45%) received a β-lactam (totaling 153 days of therapy with 5 intravenous courses for complicated infections). Conclusion: An ASP/Allergy Service collaboration to identify inaccurate penicillin allergy labels in special outpatient populations at risk for requiring antibiotics may have a positive impact on the subsequent rate of the use of first-line antimicrobials. Disclosures: All authors: No reported disclosures.